ISLAMIC KNOWLEDGE MANAGEMENT (IKM) PADA PERPUSTAKAAN PTKIN WILAYAH SUMATERA MENGHADAPI WACANA WORK FROM ANYWHERE - Resty Jayanti Fakhlina; Shinta Nofita Sari (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This paper aims to find out the Islamic Knowledge Management (IKM) Library of the state Islamic religious college (PTKIN) in the new normal era/work from anywhere. Focus on library tacit and explicit knowledge; how to deal with the era of the new normal; and manage Islamic knowledge in the future. The research method used is a qualitative method with a descriptive approach. The results of this research, first, in managing Islamic knowledge, the library began to transfer the media of Islamic library materials such as Arabic books with an Islamic approach into pdf form and the organization strengthens the psychology of workers by paying attention to workplace spirituality. The library also facilitates the needs of users for Islamic library materials and referral services through online media such as whatsapp, telegram, and email. Second, then to face the work from anywhere era, the library will prepare things directly after the Covid-19 pandemic and increase the use of information and communication technology (information and Communication Technology / ITC). Second, the PTKIN library did to improve the tacit knowledge of the staff was to use several video conferencing applications to attend webinars on information science and libraries as well as about the Islamic of staff, work groups, and organization. As for explicit knowledge, the PTKIN library during WFH encouraged its staff to be active on social media and make webinars with the theme of information science and libraries. The conclusion of this study shows that libraries can provide services for users by implementing IKM and increasing organizational knowledge during the work from anywhere period.